Sensation seeking and its relationship with psychopathic traits, impulsivity and aggression: a validation of the Dutch Brief Sensation Seeking Scale (BSSS). Issue 1 (2nd January 2022) - van Dongen, Josanne D. M.; de Groot, Manon; Rassin, Eric; Hoyle, Rick H.; Franken, Ingmar H. A.
Abstract : Sensation seeking is a personality trait that manifests as a preference for change, variety and novelty. Sensation seeking has been positively associated with different externalising behaviours. However, its associations with psychopathic traits, impulsivity and aggression are unclear. These associations were examined via the psychometric properties of the Dutch version of the Brief Sensation Seeking Scale (BSSS) using individuals from the general population and forensic patients. The results show that the BSSS has good psychometric properties, including test-retest reliability and a four-factor structure. Additionally, the results support associations between sensation seeking and psychopathic traits, impulsivity and total scores of aggression but revealed no specific associations with different types of aggression (e.g. proactive and reactive). The Dutch BSSS is a valuable tool for assessing sensation seeking in both the general population and forensic patients. Future research should further examine its utility and explore the role of sensation seeking in antisocial conduct.